2007
DOI: 10.1002/joc.1567
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of large‐scale conditions associated with convection over the Indian monsoon region

Abstract: This paper examines the thermodynamics of the atmosphere in relation to occurrence of convective rainfall over the Indian region. Various thermodynamical and kinematic parameters such as convective available potential energy (CAPE), convective inhibition energy (CINE), equivalent potential temperature and relative vorticity field are computed based on model analysis field of the limited area model of India Meteorological Department. The data period of this study is from 15 March 2001 to 28 February 2002. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 26 publications
5
44
0
Order By: Relevance
“…The mean CAPE, RH 500 , and deep-level VWS associated with the MCSs over the ocean are the strongest among all of the regions. Mean CAPE over land (∼860 J/kg) is lower than that over the ocean, consistent with previous findings based on reanalysis (39) and meteorological stations' datasets (40). RH 850 associated with the MCSs over the oceanic surface is also high.…”
Section: Resultssupporting
confidence: 90%
“…The mean CAPE, RH 500 , and deep-level VWS associated with the MCSs over the ocean are the strongest among all of the regions. Mean CAPE over land (∼860 J/kg) is lower than that over the ocean, consistent with previous findings based on reanalysis (39) and meteorological stations' datasets (40). RH 850 associated with the MCSs over the oceanic surface is also high.…”
Section: Resultssupporting
confidence: 90%
“…This is seen in most of the years studied, but more clearly for the period of 1996-2006. Roy Bhowmik et al (2008) demonstrated that the belt of maximum CAPE shifts to the southern peninsula during the post-monsoon and winter season. We found a secondary peak in CAPE during October over Kolkata that seems to be more effective in controlling the temperature at the upper troposphere.…”
Section: (B) Large-scale Variations In Cape and The Temperature Over mentioning
confidence: 99%
“…Therefore, almost simultaneously, CAPE and rainfall annual temporal variation shows a strong relationship. Roy Bhowmik et al (2008) reported that during the pre-monsoon period, CAPE enhances earlier than rainfall based on 1 year of model data. However, we could not find any convincing trend in rainfall that resembled that found in CAPE.…”
Section: (B) Large-scale Variations In Cape and The Temperature Over mentioning
confidence: 99%
See 2 more Smart Citations